Optimization of digestion method for determination of copper in shrimp paste sample using flame atomic absorption spectrometry - Yahya M.A.; Amin K.K.M.; Al-Qodah Z.; Ngah C.W.Z.C.W. (Chemical Publishing Co., 2024)
Indexed by Scopus